The EU's REFIT strategy: a new bureaucracy in the service of competitiveness? - Van den Abeele, Eric (Brussels, 2014)
" This Working Paper provides a clear but critical assessment of the EU’s process of simplification and qualitative improvement of the ‘acquis’, a process originally known as ‘Better Law-making’, subsequently as ‘Smart regulation’ and, in its latest incarnation, as ‘Regulatory Fitness and Performance (REFIT)’.